Mental Healing in Korean Drama “It's Okay to Not Be Okay - Heidy Arviani; Natasya Candraditya Subardja; Jessica Charisma Perdana (JOSAR (Journal of Students Academic Research), 2021)
This study aims to describe adult mental healing, which is represented in the Korean drama series "It's Okay to Not Be Okay" through several characters. This romance drama, wrapped in internal conflict and mental illness, has high ratings both domestically and internationally. Aired through the Netflix network, this series broke the record number of viewers and caused much controversy. This study uses a qualitative approach using semiotic analysis theory and data analysis techniques Charles Sanders Pierce. Pierce categorized the triangle of a meaning theory, which consisted of three main elements: signs, objects, and interpretants. The researcher analyzes the selection of text and images related to mental healing. The results showed that the characters in "It's Okay to Not Be Okay" experienced psychological disorders in the form of depression, anti-social, autism, hallucinations, Manic Disorder, and Post-Traumatic Stress Disorder. This drama encourages Korean people who have tended to be more aware of mental problems and the importance of healing them in the personal (non-medical) realm through the interpersonal approach of the characters. Healing techniques such as Butterfly Hug, Problem Solving Therapy, Interpersonal Therapy, and coping with past trauma are several solutions for mental healing.